Menggambar dan Mewarnai Wayang Kulit sebagai Strategi Edukasi Budaya Anak - Soni Sadono; Dyah Ayu Wiwid Sintowoko; Donny Trihanondo (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
This community service activity aims to introduce and strengthen children’s cultural education through drawing and coloring traditional shadow puppets (wayang kulit) as a creative and contextual learning medium. The activity was conducted in a mosque environment as an inclusive non-formal educational space that plays an important role in supporting children’s social, cultural, and character development within the community. The methods implemented included introducing the Pandawa characters, explaining the cultural values and moral messages contained in wayang kulit, guiding children in creating basic wayang illustrations, and facilitating coloring activities that encouraged creativity and individual expression. The participants consisted of children from Madrasah Diniyah, elementary school, and junior high school levels with different educational backgrounds and artistic abilities. The results showed an increase in children’s enthusiasm and awareness toward traditional arts and cultural heritage. Through the activity, children began to recognize character values such as honesty, courage, perseverance, responsibility, and togetherness represented by wayang characters. The activity also encouraged active participation, creativity, and an enjoyable learning experience. Therefore, drawing and coloring wayang kulit can be considered an effective strategy for implementing contextual, interactive, and sustainable cultural education for children.